2022
DOI: 10.1007/s10570-022-04881-3
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of C6-Fluorocarbon-dendrimer-based superhydrophobic cotton fabrics for multifunctional aspects

Abstract: C6-Fluorocarbon-dendrimer has been applied to the cotton knit fabric to develop oil-water repellent, oilwater separation, acid-resistant, self-cleaning, ame retardant, UV resistant, and antibacterial properties. The C6-Fluorocarbon (FC)-dendrimer-coated 100% cotton single jersey knitted fabric samples were prepared using the "pad-dry-cure" method. The 90 g/L and 100 g/L FC-dendrimer-treated cotton fabrics showed excellent water repellency and oil-water separation as well as good self-cleaning performance. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…The fluorocarbon left the fabric stiff as it cross-linked with the O-H group in the amorphous region of the cotton. In addition, since the cross-linking reaction of the fluorocarbon occurred with acetic acid added to the bath in the acidic region, it caused a decrease in strength [36][37][38]. As a result of the processes carried out according to the layer-by-layer deposition principle, it was determined that there was an increase in the breaking strength values of 5.41% for reactive dyes and 4.24% for direct dyes.…”
Section: Resultsmentioning
confidence: 99%
“…The fluorocarbon left the fabric stiff as it cross-linked with the O-H group in the amorphous region of the cotton. In addition, since the cross-linking reaction of the fluorocarbon occurred with acetic acid added to the bath in the acidic region, it caused a decrease in strength [36][37][38]. As a result of the processes carried out according to the layer-by-layer deposition principle, it was determined that there was an increase in the breaking strength values of 5.41% for reactive dyes and 4.24% for direct dyes.…”
Section: Resultsmentioning
confidence: 99%
“…Saha et al, 166 fabricated a new sorbent of knitted cotton fabric for oil-water separation via the pad-dry-cure technique (Figure 14(a)). Herein, the fabric was coated with C6- Fluorocarbon (FC)-dendrimer (Figure 14(b) and (c)).…”
Section: Applications Of Textile Sorbents For Oil Spill Cleanupmentioning
confidence: 99%
“…Whereas, the oil weight gain (%) of uncoated fabric and coated fabric was 521 ± 2.31% and 698 ± 2.65%, respectively, for engine oil. They concluded that the weight gain (%) of vegetable oil is the highest for both compared sorbents owing to its low viscosity (Figure 13 Saha et al, 166 fabricated a new sorbent of knitted cotton fabric for oil-water separation via the pad-dry-cure technique (Figure 14(a)). Herein, the fabric was coated with C6-Fluorocarbon (FC)-dendrimer (Figure 14(b) and (c)).…”
Section: Knitted Oil Cleanup Sorbentsmentioning
confidence: 99%
See 2 more Smart Citations